What makes up a reportable event in a language?: Motion events as an important test domain in linguistic typology [dataset] - Stutterheim, Christiane von; Gerwien, Johannes; Bouhaous, Abbassia; Carroll, Mary; Lambert, Monique (Universität, 2019)
Numerous cross-linguistic studies on motion events have been carried out in investigating the scope of the two-fold typology path versus manner (Talmy 1985; 2000) and its possible implications. This typological contrast is too narrow as it stands, however, to account for the diversity found within and across types. The present study is based on what can be termed a ‘process-oriented perspective’. It includes the analyses of all relevant conceptual domains notably the domain of temporality, in addition to space, and thus goes beyond previous studies. The languages studied differ typologically as follows: ‘path’ is typically expressed in the verb in French and Tunisian Arabic vs ‘manner of motion’ in English and German, while in the temporal domain ‘aspect’ is expressed in English and Tunisian Arabic but not in German and French. The study thus compares the representations which speakers construct when forming a reportable event as a response to video clips of a series of naturalistic scenes in which an entity moves through space. The analysis includes the following conceptual categories: (1) the privileged event ‘layer’ (manner versus path) which drives the selection of breakpoints for forming event units when processing the visual input, (2) the privileged category in spatial framing (figure-based/ground-based), and (3) viewpoint aspect (phasal decomposition or not). We assume that each of these three cognitive categories is shaped specifically by language structure (system and repertoire) and language use (frequency of constructions). The findings reveal systematic differences both across, as well as within, typologically-related languages with respect to (1) the basic event type encoded, (2) the changes in quality expressed, (3) the total number of path segments encoded per situation, and (4) the number of path segments packaged into one utterance. The findings reveal what can be termed language-specific default settings along each of the conceptual dimensions and their interrelations which function as ‘language specific attentional templates’.
Gesehen am 09.05.2019
Keywords: Forschungsdaten; Datenbank